Ionic Liquid-Assisted Synthesis of Nickel Oxide Magnetic Nanoparticles - Mariappan, Ramalakshmi; Mahalingam, Sundrarajan (Asian Journal of Chemistry, 2013)
In this paper, the synthesis of nickel oxide nanoparticles using a novel synthesis medium namely 1-n-butyl-3-methylimidazolium trifluoromethane sulfonate [BMIM][TfO] ionic liquid. Ionic liquids have been used as a potential electrolyte/medium for the nanoparticle synthesis, especially for their suitability at high temperature withstandability. During the NiO nanoparticle synthesis, Ni(OH)2 precipitates first consequently NiO nanoparticles is formed upon calcinations at 400 ºC. Nickel hydroxide and oxide formation was confirmed by XRD, FT-IR and TGA results of the NiO as precipitated and calcinated samples. The SEM image of the calcinated sample shows the average particle size is 45 nm with small rock salt-like morphology. The synthesized NiO nanoparticle exhibits an excellent superparamagnetic behaviour without showing any coercivity. The magnetic property of NiO nanoparticle was studied with vibrating sample magnetometer.